X-ray absorption spectroscopy set-up for unstable gases: A study of 5p hydrides. (June 2020) - Hauko, R.; Padežnik Gomilšek, J.; Kodre, A.; Arčon, I.
Abstract: An absorption cell is constructed for x-ray absorption spectroscopy of reactive, unstable or hazardous gases at room temperature. In conjunction with in-situ micro-synthesis technique relying on handling the gas in syringes it enabled a first measurement of x-ray absorption spectra in the region of K and L edges for the series of hydrides of 5 p elements (SnH4, SbH3, TeH2, HI). The signal-to-noise ratio above 10 3 was achieved, whereby fine detail is discerned in the spectra, in particular the small sharp features above each absorption edge, testifying of coexcitations of outer electrons in the core photoeffect. Highlights: Absorption cell for x-ray absorption spectroscopy of unstable gases is developed. K and L edge spectra in the series of hydrides of 5 p elements (Sn–I) are measured. With signal-to-noise ratio of 10 3 and better, the fine detail in spectra is discerned. Above the edge, the weak multielectron photoabsorption features are resolved.